Evaluation of potato hybrids for yield components in humid subtropical climate during autumn season - M. A. Khan; I. A. Hafiz; K. Farooq; N. A. Abbasi; A. Razzaq (Journal of Animal and Plant Sciences, 2014)
Owing to the importance of potato crop, fifty potato hybrids developed by potato program NARC were evaluated for quality traits and yield parameters in randomized complete block design with three replications at National Agriculture Research Center Islamabad during 2010-2011. Highly significance variation was observed for most traits of the hybrids evaluated. It was also invented to compare their performance in order to identify and select hybrids with enhanced potential for growth and yield in humid sub-tropical climate.The highest number of big size (>55mm) tubers per meter2 (5.77) was produced by clone G-136 while clone D-46 and A-12 produced minimum number (2)of big tubers per meter2 however average big tuber weight (177.06 g) was recorded in N-10, whereas the maximum medium size tubers (20.97) per meter2 were obtained from potato clone A-12, however, potato genotypes N-10 produced least number of medium tubers (7.36). Maximum weight of medium tubers was in I-32 (86.58g) and minimum weight was in D-46 (45.49 g). The maximum numbers of total tubers (45.27) per meter2 were recorded inclone I-23. The maximum average weight of total tubers was 89.46 g in clone I-32. Potato clone I-32 produced maximum percentage of marketable tubers with 94.76% followed by Clone O-17, F-24 and N-10 with 94.42 %, 93.71 % and 92.58 % respectively. Although clone I-23 produced more number of tubers than that of the I-32 but the marketable tuber percentage was less in the clone I-23. So, this study recommends the clones O-17, I-30, I-32, G-128, K-139 and F-24 for potato cultivation in humid subtropical conditions during autumn season for maximum yield.
Keywords: Solanum tuberosum; Potato; Yield; Varieties; Hybrid; Autumn; Ecological